Evaluation of isthmin-1 immunoreactivity in gastric adenocarcinoma - Ağ, Onur; Yur, Mesut; Hançer, Serhat; Bozan, Mehmet Bugra; Özercan, Ibrahim Hanifi; Kuloglu, Tuncay (Colegio Brasileiro de Cirurgia Digestiva, 2026)
Background: Isthmin-1, a recently discovered adipokine, was first characterized for its role in early brain development. Subsequent studies have demonstrated that isthmin-1 is involved in a broad range of biological processes, including metabolism, immunity, tumorigenesis, cellular proliferation, endothelial permeability, and organ development. Aims: This study aimed to evaluate isthmin-1 immunoreactivity in tumor tissues obtained from gastric cancer patients using immunohistochemistry and to assess its usefulness in the diagnosis and histological evaluation of gastric cancer. Methods: The patients were divided into three groups: adenocarcinoma, intestinal metaplasia, and healthy controls. Endoscopic biopsies, obtained according to the Sydney protocol, were examined for the control group and patients diagnosed with intestinal metaplasia. In contrast, surgical resection tissues were used for patients diagnosed with gastric adenocarcinoma. Results: All materials were examined histopathologically. No significant difference in isthmin-1 levels was detected between the control and intestinal metaplasia groups, based on immunohistochemical staining. However, when gastric adenocarcinoma cases were compared with the control and intestinal metaplasia groups, a significant decrease in isthmin-1 immunoreactivity was observed in adenocarcinoma cases. Patients with adenocarcinoma were grouped as well-differentiated, moderately differentiated, and poorly differentiated, and then staged according to the TNM staging system. Histopathological examination revealed no significant differences in the degree of differentiation or TNM stage. Conclusions: We believe that isthmin-1 can be used as a biomarker in the diagnosis of malignant gastric diseases in the future. However, more comprehensive and extensive scientific studies are needed to determine its usefulness in tumor staging or prognosis monitoring. © 2026, SciELO-Scientific Electronic Library Online. All rights reserved.
Avaliação da imunorreatividade da isthmina-1 no adenocarcinoma gástrico
Keywords: Adenocarcinoma; Adipokines; Metaplasia; Stomach Diseases; Stomach Neoplasms